2011
DOI: 10.1007/s10646-010-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of physiologically based modelling and transcriptomics to probe the systems toxicology of aldicarb for Caenorhabditis elegans (Maupas 1900)

Abstract: The toxicity of aldicarb on movement, life cycle, population growth rate and resource allocation, and the gene expression changes underpinning these effects, were investigated for Caenorhabditis elegans. A clear effect of aldicarb on nematode movement was found suggesting that this pesticide acts as a neurotoxicant. Aldicarb also had an effect on life cycle traits including low concentration life-span extension; high concentration brood size reduction and a high concentration extension of time to first egg. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…Since the 1970s, C. elegans has been used frequently for single‐species toxicity testing to evaluate effects by various substances, with mortality, behavior, reproduction, and growth as the endpoints most often applied . In general, both the range of EC50s and LC50s and the relative toxicity ranking of substances (within groups) obtained in the present study were similar to those previously reported for C. elegans , although test conditions differed in several points (e.g., tested life stage, exposure times) . Irrespective of the endpoint used, metals and carbamates possessed a comparable toxic potential and were both by far more toxic than nonpolar narcotics.…”
Section: Discussionsupporting
confidence: 88%
“…Since the 1970s, C. elegans has been used frequently for single‐species toxicity testing to evaluate effects by various substances, with mortality, behavior, reproduction, and growth as the endpoints most often applied . In general, both the range of EC50s and LC50s and the relative toxicity ranking of substances (within groups) obtained in the present study were similar to those previously reported for C. elegans , although test conditions differed in several points (e.g., tested life stage, exposure times) . Irrespective of the endpoint used, metals and carbamates possessed a comparable toxic potential and were both by far more toxic than nonpolar narcotics.…”
Section: Discussionsupporting
confidence: 88%
“…Mechanisms of action of aldicarb have been investigated using DEBtox modeling, revealing that an increase in energy demands was associated with maintenance in somatic and reproductive tissues. 81 It was found that uranium affected assimilation of energy from food and disrupted growth and reproduction in C. elegans based on the DEBtox model. 75 Taken together, although there are plausible uncertainties in the experiments and the modeling, our toxicity bioassays and the TBTK/TD modeling in worms could be extensively applied in environmental and health-risk analysis.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Toxicity endpoints recently reported include reproduction (11), feeding (12), DNA damage and repair (13, 14), and gene expression (15, 16). Despite the advantages of C. elegans as a model of development and disease, its use in developmental toxicology has largely focused on observational rather than mechanistic studies (17).…”
Section: Introductionmentioning
confidence: 99%